Notch signaling in prostate cancer: A moving target. Issue 9 (16th April 2014) - Carvalho, Filipe L. F.; Simons, Brian W.; Eberhart, Charles G.; Berman, David M.
<x xml:space="preserve">Abstract</x> INTRODUCTION By regulating cell fate, proliferation, and survival, Notch pathway signaling provides critical input into differentiation, organization, and function of multiple tissues. Notch signaling is also becoming an increasingly recognized feature in malignancy, including prostate cancer, where it may play oncogenic or tumor suppressive roles. METHODS Based on an electronic literature search from 2000 to 2013 we identified, summarized, and integrated published research on Notch signaling dynamics in prostate homeostasis and prostate cancer. RESULTS In benign prostate, Notch controls the differentiation state and architecture of the gland. In prostate cancer, similar features correlate with lethal potential and may be influenced by Notch. Increased Notch1 can confer a survival advantage on prostate cancer cells, and levels of Notch family members, such as Jagged2, Notch3, and Hes6 increase with higher cancer grade. However, Notch signaling can also antagonize growth and survival of both benign and malignant prostate cells, possibly through antagonistic effects of the Notch target HEY1 on androgen receptor function. DISCUSSION Notch signaling can dramatically influence prostate development and disease. Determining the cellular contexts where Notch promotes or suppresses prostate growth could open opportunities for diagnostic and therapeutic interventions. Prostate 74:933–945, 2014. © 2014 Wiley Periodicals, Inc.